Development of The Child Inmates of Drug Cases in The Institute of Coaching Special Children - Waldi; Nurjannah, St.; Jumadi (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the child development system of narcotics cases in children's special training institutions (LPKA) in Maros Regency and identify the inhibiting factors in the implementation of coaching in the LPKA. The method used normative way. The results showed that the coaching system for narcotics students in LPKA is not specifically structured, and lack of attention to special cases such as narcotics. Children who enter LPKA generally do not receive rehabilitation before, even though this is required by Law Number 35 of 2002 concerning child protection. Other inhibiting factors include the lack of faculty to provide formal education and special assistance to children involved in narcotics cases. In this context, the improvement of the coaching system and handling of narcotics cases in LPKA needs to be improved to provide more effective protection and coaching for students.